Accidentes ocupacionales en empresas mineras a pequeña escala en Colombia: un estudio de los retos y oportunidades para la prevención y protección de los trabajadores mineros. (2024)
This monograph was executed with the purpose of investigating which are the most recurrent work accidents in small-scale mining within the department of Cundinamarca, in order to expand information available from the last 10 years, from the different studies carried out by various entities. public such as the Ministry of Labor, the National Mining Agency; the academy “university research”; mining sector associations and other publications of a particular type "blogs, internet pages, etc.", in order to determine good skills and recommendations for workers in small-scale mining in accident prevention,